Measurement of the logistic customer service level in commercial cargo motor transport companies - Kadłubek, Marta (Logistics and sustainable transport, 2014)
The term of logistic customer service is defined as the abilities or skills to meet the customer's requirements and expectations, chiefly in terms of the time and place of deliveries, while using all available forms of logistic activity, including transport, storage, and the management of inventories, information and packages. As eac h of the logistic activities has an effect on the customer receiving right product or service, in its proper condition, in the correct time and space, and at reasonable costs, so seeking the proper service comes down to managing logistic activities in such a manner, as to achieve the essential level of customer satisfaction at the lowest possible costs. The identified elements of logistic customer service in an organization are placed on a specific level, as assessed from the perspective of the purchasers' expectations. Among various methods for measuring customer service level, or quality, which are described in the literature on the subject, the SERVQUAL is recognized as one of the most effective. The SERVQUAL method relies on measuring the differences th at exist between the quality, as perceived by a customer, and the quality demanded by that customer from a specific service. In order to determine the difference, both the customer's expectations for the service level, and their fulfilment by a specific or ganization need to be examined at the same time. The elements of logistic customer service of the Silesian Province's (region in southern Poland) commercial cargo motor transport enterprises under study are placed on a measurable level, as evaluated from t he perspective of the recipients of offered transport services. The measurement of the logistic customer service level, as found in the entities examined, was made using the SERVQUAL method. The survey questionnaire used in the study was constructed based on 22 logistic customer service determinants. Questionnaire forms were filled by 294 customers of 147 Silesian Province's commercial cargo motor transport enterprises examined, i.e. two customers of each enterprise. The article presents theoretical basis for the measurement of the logistic customer service level by the SERVQUAL method, description of acquiring the research material, analysis of examination results and conclusions.
Keywords: kakovost; logistika; storitve; transport